Algumas implicações pedagógicas da epistemologia de Piaget - Mendes, Elise Barbosa (1995)
This work is about Piagefs epistemology and also about educational systems based on it. The author presents a short account of Piagefs life and of the origin of his scientific ideas. On analyses his view that there is a relationship between organic and mental life. On also points out the analogy between the structuralism of the mathematician N Boubarki and Piagefs cognitive models. The reader will see that this analogy was noticed by Piaget himself. Besides, this monography tryes to clarify the interactive aspects os Epistemology and shows the necessity of understanding both the structure of the subject and of the object of Knowledge. The author makes her best to justify the use of Genetic Epistemology in the pedagogical practice and theory. In doing so, she aims at demonstrating that a pedagogical practice based on the systemic structuralism of Piaget is likely to reach the goals of moral and intelectual development. Last but not least, the reader, who perseveres til the end of this work, will find a sketchy evaluation of a few educational experiences whose foundations lays on one or another of Piagefs hypothesis. The works of Papert and Kamii are among the above mentioned experiences together with educational methods which, although not directly related to Piagefs propositions, the Swiss psychologist considered akin to his own ideas.